HTML 4.0 : user's resource - Murray, William H., 1943-.; Pappas, Chris H., 1953-. (Upper Saddle River, NJ : Prentice Hall PTR, 1998)
Quick, get me started - what is HMTL? URI's and Web browsers; Layout of a simple HTML document; HTML HEAD, BODY, and SCRIPT elements; Text and lists; Images; Multimedia; Tables; Links and anchors; Image maps; Forms; Style sheets; Scripts; Frames; Objects; Layers and layering; Dynamic HTML.
Includes index.
Keywords: Computers; HTML (Document markup language).; World Wide Web